MODELING OF TRAFFIC-LIGHT SIGNALIZATION DEPENDING ON THE QUALI-TY OF TRAFFIC FLOW IN THE CITY - Aleksandr, Novikov; Ivan, Novikov; Anastasiya, Shevtsova (Journal of Applied Engineering Science, 2019)
The high level of motorization typical for many cities gives background to the emergence of satarovich situations, which largely reduces the transporting access to and unimpeded movement. To resolve occurring traffic problems are used for various kinds of activities that subunits are radical and conservative. For existing cities, quite often used the second type of events that do not require significant capital investments compared to the first one of these activities is improvement of traffic lights regulation, to reduce delays to vehicles by changing the input parameters required in the calculation. In this work the authors is proposed to model the traffic signalization traffic flow based on its qualitative composition. The growth of car ownership contributes to the change in the qualitative composition of traffic flow, that is not to be taken in determining the modes of traffic lights regulation. The authors performed a study of urban traffic, the results of which allowed to determine the values of the distributions of vehicles in the stream with regard to its composition, based on the extension of the main rolling stock type – passenger car. Based on the obtained distributions, a mathematical analysis for determining the influence of each considered class and refined method of calculation of the traffic signalization. The purpose of the proposed assessment to the development of a methodology for calculating the experimental computer simulation, the comparative analysis of the obtained data and the main conclusions of the study.